The Impacts Of Port Characteristics And Port Logistics Integration On Port Performance In Ethiopian Dry Ports - Endris Ali; Abate Ayelign (Goodwood Publishing, 2022)
Purpose: This paper identifies the impacts of port characteristics and port-logistics integration on port performance in the case of Ethiopian dry ports. Research Methodology: To complete the study, we used structural equation modeling to test the relationship between port characteristics and port-logistics integration with port performance. Moreover, Statistical Package for Social Science is also used to filter indicators. Apart from this, the study was conducted in three dry ports of Ethiopia having a sample of 279 employees. Results: The finding shows that port characteristics such as port infrastructure, port connectivity, and port privatization have significantly impacted port performance. Also, port-logistics integration has an impact on both port operational performance and port efficiency. Limitations: The main limitation is that the study focused only on three dry ports of Ethiopia which do not include other dry ports in the country. Contribution: Ethiopia suffered forced dependency on transit countries after a blooded war with Eritrea which resulted in customs delays at port. To reduce this, the study suggests that Ethiopia should coordinate in developing joint infrastructures, and formulating unfettered rules and regulations with its transit countries.